Correction of phase drifts in two-wavelength digital holographic microscopy using secondary reference waves - Šarbort Martin; Čížek Martin; Pavelka Jan; Lazar Josef (EPJ Web of Conferences, 2024)
We present a two-wavelength digital holographic microscopy setup for surface topography measurement with single-point illumination and a method for correction of unwanted phase drifts using secondary reference waves.